Psychometric analysis of lecturers’ self-efficacy instrument - Velu, Jeya; Nordin, Mohamad Sahari (Higher Education Research and Development Society of Australasia, 2011)
The Lecturers’ Self-Efficacy instrument was administered to 106 lecturers in a Teacher Education Institute. About 36.8% of the respondents are male and 63.2% are female. The aim of this study is to test the psychometric properties of Lecturers’ Self-Efficacy instrument (LSE). The LSE with 80 items measures self-efficacy and it uses anchors of ‘not confident at all’ and ‘very confident’ on a 7-point scale. The data derived from a teacher training institution were subjected to Principal Component Analysis with Varimax rotation. The analysis extracted three distinct factors: (1) teaching, (2) research and (3) service. These three factors explained most of the variance (69.39%). The reliability coefficient was determined using Cronbach Alpha that showed the coefficient is .98. The results clearly documented that LSE has adequate convergent validity and discriminant validity as well as high level of construct reliability. Practical implications and direction for future research using the LSE for lecturers are also discussed.